The Impact of Monetary Policy on the Fintech Industry in Indonesia: Growth, Consumer Behavior, and Financial Inclusion - Putri, Febiolany Amelia (Law and Economics, 2024)
This research examines the impact of monetary policy on Indonesia's fintech industry, focusing on how changes in policy affect fintech growth, consumer behavior, and financial inclusion. Using a mixed-methods approach that combines quantitative data analysis with qualitative insights from industry stakeholders, the study finds a significant correlation between accommodative monetary policy characterized by lower interest rates and increased fintech lending, as well as greater consumer adoption of digital financial services. This growth notably benefits underserved populations, showcasing fintech's potential to enhance financial inclusion. However, the research also identifies challenges, such as the tendency for increased risk-taking during low-interest periods and the need for effective risk management practices. Furthermore, the study underscores the necessity for adaptive regulatory frameworks to protect consumers and maintain financial stability. Based on these findings, several policy recommendations are proposed to cultivate a supportive environment for fintech innovation while addressing the challenges associated with monetary policy changes. Overall, this research deepens the understanding of the relationship between monetary policy and the fintech sector, providing important insights for policymakers, industry stakeholders, and future research endeavors.